Tinjauan Konstitusional atas Kewenangan KPK dalam Perkara Korupsi Koneksitas Pasca Putusan MK. No. 87/PUU-XII/2023 - Warow, Gregorius Excelcis (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
This research aims to examine the authority of the Corruption Eradication Commission (KPK) in handling connectivity corruption cases after the Constitutional Court Decision Number 87/PUU-XXI/2023. This research is a normative legal research with a statute approach and a case approach, using primary and secondary legal materials collected through literature studies. The results of the study show that the Constitutional Court interpreted Article 42 of the KPK Law constitutionally conditionally, so that the KPK remains authorized to handle connectivity cases as long as the handling begins from the beginning by the KPK. This decision provides legal certainty as well as strengthening legitimacy for the KPK in handling cases involving legal subjects from the general and military courts at the same time. This study also shows that structural barriers, multi-interpreted legal substance, and sectoral legal culture are serious challenges in connectivity law enforcement practices. Therefore, it is necessary to harmonize regulations and strengthen the legal structure and culture between institutions in order to realize a more effective, fair, and non-discriminatory eradication of corruption.